2011
DOI: 10.3892/ijo.2011.1143
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of EGFR in the promotion of malignant properties in multidrug resistant breast cancer cells

Abstract: Abstract. Multidrug resistance is the most predominant phenomenon leading to chemotherapy treatment failure in breast cancer patients. Despite many studies having suggested that overexpression of epidermal growth factor receptor (EGFR) is a potent predictor of malignancy in cancers, systematic research of EGFR in multidrug resistant (MDR) breast cancer cells is lacking. In order to clarify the role of EGFR in MDR breast cancer cells, MCF7/Adr expressing relatively higher EGFR, and its parental cell line MCF7 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 23 publications
(26 reference statements)
1
34
0
Order By: Relevance
“…For example, incubation of human-derived PancCa tumor cell lines with standard of care agents such as gemcitabine, 5-fluorouracil, and cisplatin results in an elevation of MDR protein expression in surviving cells [4] and MDR-based resistance to frontline agents in breast cancer therapy is a well-established fact [5, 6]. One clinical strategy to overcome MDR is to co-administer inhibitors of MDR transport with the objective of increasing intracellular concentrations of the chemotherapeutic agents and achieving required therapeutic exposure [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, incubation of human-derived PancCa tumor cell lines with standard of care agents such as gemcitabine, 5-fluorouracil, and cisplatin results in an elevation of MDR protein expression in surviving cells [4] and MDR-based resistance to frontline agents in breast cancer therapy is a well-established fact [5, 6]. One clinical strategy to overcome MDR is to co-administer inhibitors of MDR transport with the objective of increasing intracellular concentrations of the chemotherapeutic agents and achieving required therapeutic exposure [27].…”
Section: Discussionmentioning
confidence: 99%
“…MDR contributes to the poor response to frontline treatment of PancCA [3], as enhanced expression of MRP-1, MRP-3 and MRP-5 has been associated with resistance to gemcitabine and 5-fluorouracil [4]. In the treatment of breast cancer, over 80% of the breast cancer patients who receive chemotherapy will relapse with the eventual development of MDR disease primarily associated with overexpression of Pgp, MRP1 and BCRP [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This integrative approach has been, however, less widely used in inflammatory models. For IBD [64] and many other autoimmune diseases including Sjogren’s disease [65], we are still at the stage of documenting differential expression levels of miRNAs between disease and control cohorts.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Therefore, the development of gene-targeted therapy for breast cancer requires further attention. Previous studies have revealed that numerous genes are involved in the occurrence and development of breast cancer, including cyclin D1, matrix metalloproteinases (MMPs) and E-cadherin (5)(6)(7)(8). Astrocyte elevated gene-1 (AEG1) has also been investigated with respect to poor prognosis in breast cancer (9).…”
Section: Introductionmentioning
confidence: 99%